Ranking efficiency of rural property investment projects using multicriteria decision methods/Daugiakriterinis kaimo statinių investicinių projektų, efektyvumo vertinimas - Lunkevičius, Sigitas; Ustinovičius, Leonas; Zavadskas, Edmundas Kazimieras (Journal of Civil Engineering and Management, 2001)
Many researchers are right considering economic effect of investments as the key indicator, however, ranking other social, ecological and technical indicators of efficiency separately and leaving them outside of investment ranking criteria system. The authors suggest using together all known efficiency criteria plus some specific of rural property: Payback period, Net present value, Internal rate of return, Profitability index, Business perspective, Rural property purchase price, Rural property reconstruction price, Number of workspace, Taxes, Social level of villagers, Fascination of village. Ranking rural property investment project does not mean deciding which criterion is preferred to another one. Therefore in this situation we use ELECTRE IV approach, because it's objective is to rank the options, but without any weighting criteria. The authors have made some alternatives of rural property revival: Heating and airing systems factory, Fish products manufacture, Woodworker manufacture. On the basis of calculation results the following partial ranking of the alternative projects is suggested: 1. Fish products manufacture; 2. Heating and airing systems factory; 3. Rural property; 4. Woodworker manufacture; 5. Sport and leisure centre.Article in Lithuanian.First Published Online: 30 Jul 2012